Cultural ecosystem services of visited landscapes An exploratory comparative study - Smith, Melanie (Socio.hu Társadalomtudományi Szemle, 2018)
Academic interest in ecosystem services has been growing in the past ten years with an increasing number of research studies and papers being dedicated to this complex and diverse field of enquiry. The Millennium Ecosystem Assessment (MEA 2005) suggested that cultural services and values were not recognised enough in landscape planning and management. This paper therefore focuses on Cultural Ecosystem Services (CES), one of the four main categories of ecosystem services (MEA, 2005). Cultural Ecosystem Services (CES) include aesthetics, cultural heritage, inspiration, spirituality, sense of place, tourism, recreation and education. Although previous research on CES has placed emphasis on the importance of human perceptions in CES and landscape research (Daniel et al. 2012), this study proposes a new research tool for doing so. The tool is a quantitative questionnaire, whose design was based on a Cultural Ecosystem Services framework. It is argued that the data can provide some interesting insights into the values and benefits that can be derived from different types of landscapes. Unlike previous CES research, this study focuses on all categories of CES simultaneously. It also attempts to differentiate between the benefits derived from different landscape types by collecting data on visitor perceptions, a hitherto under–researched area in this field. Keywords: cultural ecosystem services, landscapes, benefits, visitors